MODEL PENGAJARAN TANPA TUJUAN [ NON DIRECTIVE ] DALAM PEMBELAJARAN DI SEKOLAH DASAR PRINSIP, KARAKTER, DAN IMPLIKASINYA TERHADAP PENGEMBANGAN DIRI SISWA - EUIS WIDYANINGRUM (CV. ADIBA AISHA AMIRA, 2026)
This study examines the implementation of the Non-Directive Teaching Model within the context of elementary education, a level of schooling traditionally dominated by authoritarian instructional approaches and the pursuit of rigid competency-based curricular targets. The Non-Directive Model, rooted in Carl Rogers' humanistic psychological theory, prioritizes students' personal and emotional growth over mere cognitive transfer. The discussion in this article highlights a fundamental shift in the teacher's role from an